Lustrum study of labour induction - Sawant, Prabha P.; Chaudhari, Shilpa N.; Hol, Kishorkumar; Shastri, Shraddha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The rate of labor induction is steadily increasing. Approximately one out of four pregnant women has their labor induced. Over the years, various professional societies have recommended the use of induction of labor in circumstances in which the risk of waiting for the onset of spontaneous labor are judged by clinicians to be greater than the risks associated with shortening duration of pregnancy by induction. This study was carried out to categories indications and to know trends of indication over 5 years. Methods: This retrospective analytical study was conducted over a period of five years from 01 June 2016 to 31 May 2021 at the department of obstetrics and gynecology, tertiary care hospital, Pune, Maharashtra, India. The rate, indications and trend in indications of labor induction was calculated over the study period. The data so collected was presented with graphical representation. Results: There was a total of 10407 deliveries during the study period out of which, 865 were induced. So, the rate of labor induction in the study was found to be 8.31%. Post-datism accounts for 54.4% followed by pregnancy induced hypertension remains the major obstetric cause accounting for 16.6% of labour induction. Intrauterine growth restriction (IUGR) accounted for 3.6% causes of labour induction. Conclusions: Vaginal birth has lesser morbidity and mortality involving both the mother and the child compared to caesarean and will always be regarded as the superior mode of delivery. Apart from post-datism, the commoner obstetric indications for induction of labour are PIH and IUGR. Increasing trend in the incidence of pregnancy-induced hypertension (PIH) and IUGR is observed and therefore probably correlating to foetal distress after induction of labour causing increased trend of need for caesarean section over the five years.